2022
DOI: 10.1002/adfm.202203439
|View full text |Cite
|
Sign up to set email alerts
|

Data‐Driven High‐Throughput Rational Design of Double‐Atom Catalysts for Oxygen Evolution and Reduction

Abstract: Surging interests exist in double‐atom catalysts (DACs), which not only inherit the advantages of single‐atom catalysts (SACs) (e.g., ultimate atomic utilization, high activity, and selectivity) but also overcome the drawbacks of SACs (e.g., low loading and isolated active site). The design of DACs, however, remains cost‐prohibitive for both experimental and computational studies, due to their huge design space. Herein, by means of density functional theory (DFT) and topological information‐based machine‐learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 68 publications
(84 reference statements)
1
58
0
Order By: Relevance
“…Metal B can be then selected based on Figures a,b and so that it should have a lower decomposition energy barrier, a lower stability on the carbon surface, a lower diffusion barrier, and a synthesis temperature in step 2 lower than that in step 1. All transition metal DACs considered in this study can be stably trapped on a defective carbon surface, as shown in a recent study …”
Section: Resultssupporting
confidence: 63%
See 4 more Smart Citations
“…Metal B can be then selected based on Figures a,b and so that it should have a lower decomposition energy barrier, a lower stability on the carbon surface, a lower diffusion barrier, and a synthesis temperature in step 2 lower than that in step 1. All transition metal DACs considered in this study can be stably trapped on a defective carbon surface, as shown in a recent study …”
Section: Resultssupporting
confidence: 63%
“…All transition metal DACs considered in this study can be stably trapped on a defective carbon surface, as shown in a recent study. 33 To close the design loop of the proposed DAC synthesis strategy, we demonstrate the formation process of Pt−Au DACs on a defective carbon surface, through MD simulations (see the Methods section for details), as illustrated in Figure 4. The formation of Pt SACs on a defective carbon surface has been successfully demonstrated previously in both experiments and simulations at a temperature of 1500 K (Figure 2a predicts the lowest synthesis temperature of 1375 K).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations